2006
DOI: 10.1086/505554
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Placement among Children in Foster Care: A Longitudinal Study of Child and Case Influences

Abstract: Using Cox regression modeling, this longitudinal study examines child and case characteristics associated with changes in placement among 5,909 Rhode Island children in foster care. Results suggest that half of all children experience at least one placement change while in care. Infants change placements least, and risk increases with child age. Emergency shelter settings have the highest risk of placement change, followed by nonrelative settings, group home settings, and relative foster care. The reasons for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(54 citation statements)
references
References 33 publications
3
48
2
1
Order By: Relevance
“…As is the case with poverty, disruptions in caregiving are also known to be associated with poorer health outcomes (34)(35)(36). The majority of studies describing stability of nonparental care arrangements has been among children in foster care and suggests that more than half of children in foster care experience at least one placement change and more than one-third experience two or more placement changes while in foster care (37)(38)(39). Annual rates of placement change across children in foster care are estimated to be between 0.55 and 0.62, with some children changing placements multiple times per year (40,41).…”
Section: Instability Nonparental Care and Healthmentioning
confidence: 99%
“…As is the case with poverty, disruptions in caregiving are also known to be associated with poorer health outcomes (34)(35)(36). The majority of studies describing stability of nonparental care arrangements has been among children in foster care and suggests that more than half of children in foster care experience at least one placement change and more than one-third experience two or more placement changes while in foster care (37)(38)(39). Annual rates of placement change across children in foster care are estimated to be between 0.55 and 0.62, with some children changing placements multiple times per year (40,41).…”
Section: Instability Nonparental Care and Healthmentioning
confidence: 99%
“…Another manifestation of this relationship is found between the current age of the child and the likelihood of the placement disrupting. Older children were significantly more likely to have their placements disrupt (Smith, Stormshak, Chamberlain, & Whaley, 2001) and had a significantly higher placement change rate (Connell et al, 2006). Significant positive coefficients have also been found between the child's current age and a retrospective measure of past placements (Pardeck, 1984).…”
Section: Correlates Of Placement Instability Demographic Characteristicsmentioning
confidence: 88%
“…In the event history analysis by Connell et al (2006) with a Rhode Island sample, the risk of placement change for children in nonrelative care was 3.18 times that of children in relative care. In a recent study that matched children by age, gender, ethnicity, and geographic area, children placed with relatives or kin experienced, on average, 1.62 placements compared with 2.27 placements for those placed with nonrelatives, a statistically significant difference (Winokur et al, 2008).…”
Section: Kinship and Nonkinship Foster Carementioning
confidence: 97%
“…Many studies have found that children placed with relatives or kin experienced fewer placements than those in family foster care with nonrelatives (Connell et al, 2006;Koh, 2008;Koh & Testa, 2008;Rubin et al, 2008;Winokur, Crawford, Longobardi, & Valentine, 2008;Wulczyn, Kogan, & Jones Harden, 2003). In the event history analysis by Connell et al (2006) with a Rhode Island sample, the risk of placement change for children in nonrelative care was 3.18 times that of children in relative care.…”
Section: Kinship and Nonkinship Foster Carementioning
confidence: 99%